2020
DOI: 10.1002/uog.21980
|View full text |Cite
|
Sign up to set email alerts
|

Cordocentesis‐associated fetal loss and risk factors: single‐center experience with 6650 cases

Abstract: Objectives To identify procedural risk factors associated with fetal loss following cordocentesis and to determine the rate of cordocentesis‐related fetal loss associated with the current cordocentesis protocol used in our institution. Methods This was a retrospective cohort study of pregnancies that underwent midpregnancy cordocentesis in a single center (a tertiary hospital, teaching school), between 1992 and 2018, based on data retrieved from our prospective database. All consecutive cases were validated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
1
16
1
1
Order By: Relevance
“…Despite our concerns about the findings of their study 1 , we agree with Tanvisut et al . that, in current standard practice, cordocentesis is a relatively safe procedure associated with a fetal‐loss rate of less than 1%.…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…Despite our concerns about the findings of their study 1 , we agree with Tanvisut et al . that, in current standard practice, cordocentesis is a relatively safe procedure associated with a fetal‐loss rate of less than 1%.…”
Section: Figuresupporting
confidence: 89%
“…Fetal blood sampling in mid-pregnancy: does it still have a role in prenatal diagnosis? Tanvisut et al recently reported their single-center experience with invasive prenatal diagnosis using cordocentesis in mid-pregnancy 1 . In 6650 procedures performed at 16-24 weeks' gestation during a 27-year period, they reported a cordocentesis-related fetal loss rate of 0.6%, much lower than that observed in previous studies 2,3 .…”
mentioning
confidence: 99%
“…Abnormal ultrasound findings in the second and third trimesters of pregnancy allow the detection of a unique group of late developmental manifestations, including major and minor fetal abnormalities or ultrasound soft markers, which do not exist in the first trimester of pregnancy 5 . Because of the lack of technical expertise in hospitals, obstetric ultrasound examination is only carried out in the second and third trimesters of pregnancy and some structural abnormalities are found only later with fetal development, thus resulting in a missed examination time for chorionic villus sampling and amniocentesis (Typically, chorionic villus sampling is performed at 10–12 weeks’ gestation, and amniocentesis is performed at 15–18 weeks’ gestation).…”
Section: Introductionmentioning
confidence: 99%
“…37,38 However, cordocentesis has become almost a lost skill in Denmark due to the relatively high risk of procedure-induced fetal loss, [39][40][41] although a recent paper reports a risk of fetal loss <1% in practiced hands. 42 Potentially, cordocentesis is a procedure to be considered in cases of T8M in the CVS, if there are no malformations detected, but where the couple wish for a very low residual risk.…”
Section: Discussionmentioning
confidence: 99%